Affiliate Stigma among family caregivers of individuals with dementia in China: a cross-sectional study - Yingying Shi; Shishi Dong; Zhiqi Liang; Mengting Xie; Hanyi Zhang; Sixie Li; Jufang Li (Frontiers Media S.A., 2024)
BackgroundAffiliate stigma experienced by family caregivers of individuals with dementia may seriously affect home care and prognosis of these patients. This study aimed to explore the levels of perceived affiliate stigma and its influencing factors among family caregivers of patients with dementia in mainland China, which remains a relatively unexplored topic.MethodsIn this cross-sectional study, purposive sampling was used to recruit dementia family caregivers from an online communication group between April and May 2022. A total of 727 eligible caregivers were included and asked to complete the demographic questionnaire, the affiliate stigma scale, and the caregiver burden inventory. Descriptive statistics, independent sample t-test, one-way analysis of variance, Pearson correlation analysis, and multiple linear regression were used to explore the factors that influence perceived affiliate stigma among dementia family caregivers.ResultsThe mean score for affiliate stigma of dementia family caregivers was 48.09 ± 16.38 (range: 22-86). Whether there were regular breaks during patient care, time-dependent burden, developmental burden, physical burden, and social burden were significant factors influencing the affiliate stigma of dementia family caregivers.ConclusionDementia family caregivers showed a moderate to high level of affiliate stigma. Those who had regular breaks during patient care, higher time-dependent burden, developmental burden, and physical burden and lower social burden exhibited higher levels of affiliate stigma.